Goal-setting and digital competencies as key elements of company development management system based on information and communication technologies - A. V. Veretyokhin (Вестник университета)
Digitalization is a popular and rather complex direction of modern company development. The article is devoted to justifying the relevance of managerial goal-setting and the need to form digital competencies of employees, as well as their features and provision in the management system of company development based on information and communication technologies. The study uses methods of analysis and synthesis of scientific literature and empirical data. The article summarizes the data of scientific and practical research to identify the main advantages of the company digitalization and the problems of its implementation. The author presents the popular goals of enterprise digital transformation. Using the modern information analysis of competent organizations, the author has constructed the model to justify the goals of the company digital development. The article provides suggestions for the development of digital competencies of company personnel.